D.I.Y Speaker: Innovation of generation / Badrul Alif Mohd Asri ... [et al.] - Mohd Asri, Badrul Alif; Mohd Yusof, Nur Asilah; Noor Zaimi, Nurul Farhanah; Mohd Shair, Nur Izzatie (2021)
As we know, recycling is quite crucial for us to protect the health of our environment. Recycling is known as the process of transformation of waste materials into new materials. This term also covers waste material energy recovery. It is determining its recyclability that a material can recover the attributes it had in its initial status. It is a greener alternative to "conventional" resource-saving and greenhouse gas emission reduction management. Recycling may assist minimize losses of potentially useful substances and reduce fresh raw materials usage, reduce energy usage and air pollution, and water pollution. For example, the used bureau paper would become new office paper and polystyrene foam would be changed into fresh polystyrene. The recycling of such items, such as cans, allows them to be eternally recycled without losing their purity. However, as compared to the production of the same product from raw materials or other sources, frequently this is difficult to or prohibiting expense, many products and materials are recycled by re-using them for the production of new materials like paperboards, newspapers, papers, etc. In terms of contributing to environmental preservation, recycling is highly significant.